Fabrication and characterization of graphene-based immunosensor - Sanober, Fahmi; Wan Salim, Wan Wardatul Amani (IIUM Press, International Islamic University Malaysia, 2017)
Escherichia coli O157:H7 is a significant water contaminating agent which cause infection and release shiga toxin into host intestine. Shiga toxin can cause hemolytic uremic syndrome (HUS) and even death. Peninsular Malaysia’s eastern coast is normally affected flood almost every year. The presence of three pathogenic bacteria such as Escherichia coli, Salmonella typhimurium, and Shigella flexneri was reported in the flood water of Pahang. E. coli with a concentration of 671 CFU/mL was found in Pahang’s flood water. Moreover, E. coli O157:H7 cause 73,000 infections in the United States annually. Current amperometric-based biosensors need to be highly sensitive, specific, and with a low detection limit.